The Role of Rehabilitation in Patients With Progressive Supranuclear Palsy: A Narrative Review. Issue 6 (31st January 2018) - Intiso, Domenico; Bartolo, Michelangelo; Santamato, Andrea; Di Rienzo, Filomena
Abstract: Progressive supranuclear palsy (PSP) is a progressive neurodegenerative disorder caused by the deposition of abnormal proteins in neurons of the basal ganglia that limit motor ability, resulting in disability and reduced quality of life. So far, no pharmacologic therapy has been developed, and the treatment remains symptomatic. The aim of the present study is to perform a systematic investigation of the literature, and to determine the types and effects of rehabilitative interventions used for PSP. A search of all studies was conducted in MEDLINE/PubMed, the Cochrane Central Register of Controlled Trials, CINAHL, and EMBASE. Twelve studies were identified, including 6 case reports, 3 case series, one case‐control study, one quasi−randomized trial (i.e. not truly random) with crossover design, and one randomized controlled trial, with 88 patients investigated overall. Rehabilitative interventions varied in type, number, frequency, and duration of sessions. The most commonly used clinical measures were the Progressive Supranuclear Palsy Rating Scale (PSPRS) and Unified Parkinson's Disease Rating Scale (UPDRS). Physical exercises were the main rehabilitative strategy but were associated with other interventions and rehabilitative devices, in particular treadmill and robot‐assisted gait training. All studies showed an improvement in balance and gait impairment with a reduction of falls after rehabilitation treatment. Because of poor methodological quality and the variety of rehabilitative approaches including different and variable strategies, there was insufficient evidence of the effectiveness of any specific rehabilitation intervention in PSP. Despite this finding, rehabilitation might improve balance and gait, thereby reducing falls in PSP patients. Level of Evidence: IV